The All‐Seeing: Fraternity and Vision of God in Nicholas of Cusa. (15th July 2019) - Falque, Emmanuel
Abstract: "I am because you look upon me." This phrase from Nicholas of Cusa's De visione Dei sive De icona is enough to sum up the stakes and originality of this treatise sent in 1453 to the Tegernsee monks. "Speaking in order to see, " "seeing in order to speak, " and "hearing in order to believe" chart the different stages of this unique experience, at once aesthetic, philosophical, spiritual, and mystical. Whereas one might have believed that the mere call to transcendence would be enough to justify gathering together before God, the collective contemplation of Rogier van der Weyden's painting by the community of monks instead allows one to see and even hear that "the revelation of the witness" (and thus "the revelation of the brother") validates the truth of this communally shared experience. Reaching the "wall of paradise" does not so much mean "escaping through the wall" or "getting over the wall" as it does "inhabiting the boundary" where opposites "coincide" and man and God meet within a human community.